Model Nomenklatur Diagnosa Kebidanan Dalam Kehamilan - Melinda Rosita Wariyaka; Namsyah Baso (FORIKES, 2021)
The diversity in writing the nomenclature of midwifery diagnoses in pregnancy by midwives and the absence of guidelines from the profession is an issue that was discussed when documenting care as a characteristic of midwives as a profession. The existence of WHO recommendations about diagnoses that are not diverse and long made an idea for researchers to develop a nomenclature model of obstetric diagnoses in pregnancy. The aim is to analyze the application of the nomenclature model of obstetric diagnosis in pregnancy. This research was a cross sectional descriptive study of 49 midwives who are eligible to work in 5 pregnant community health clinics in Kupang city. The results of the Chi-square analysis stated that all models of midwifery diagnostic nomenclature in pregnancy could be applied by midwives but there was no significant relationship (p>0.05) between the midwifery diagnostic nomenclature model in pregnancy with the implementation of care by midwives. There is an influence between the level of education and length of work with these results. Keywords: diagnosis nomenclature; pregnancy; midwife ABSTRAK Keberagaman penulisan nomenklatur diagnosis kebidanan pada kehamilan oleh bidan dan tidak adanya pedoman dari profesi menjadi isu yang dibahas dalam pendokumentasian asuhan sebagai ciri khas bidan sebagai suatu profesi. Adanya rekomendasi WHO tentang diagnosis yang tidak beragam dan lama menjadi ide bagi peneliti untuk mengembangkan model nomenklatur diagnosis kebidanan pada kehamilan. Tujuannya adalah untuk menganalisis penerapan model nomenklatur diagnosis kebidanan pada kehamilan. Penelitian ini merupakan penelitian cross-sectional terhadap 49 bidan yang memenuhi syarat untuk bekerja di 5 puskesmas di Kota Kupang. Hasil analisis Chi-square menyatakan bahwa semua model nomenklatur diagnostik kebidanan pada kehamilan dapat diterapkan oleh bidan, tetapi tidak terdapat hubungan yang signifikan (p> 0,05) antara model nomenklatur diagnostik kebidanan pada kehamilan dengan pelaksanaan asuhan oleh bidan. Ada pengaruh antara tingkat pendidikan dan lama kerja dengan hasil tersebut. Kata kunci: nomenklatur diagnosis; kehamilan; bidan